SBAs for the MRCS part A : a Bailey & Love revision guide - Elwell, Vivian A.; Fishman, Jonathan M.; Chowdhury, Rajat (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
The four Surgical Royal Colleges have recently received approval from the GMC to make changes to the MRCS Part A Examination. The second edition of this popular book,SBAs and EMQs for the MRCS Part A is an invaluable guide to sitting and passing the new MRCS examination.There is an increased emphasis on Anatomy and Basic Sciences,which now account for 60% of the exam. College-approved,systematic and coherent questions for all the main systems are included, providing comprehensive coverage of the curriculum. The Question and Answer format, including many more Single Best Answers aids revision.Expanded to reflect the new 2017curriculum
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Surgery -- Examinations, questions, etc; MEDICAL / Surgery / General